Organisational culture at a South African food service company - A. Thomas; D. Lindsay (South African Journal of Business Management, 2003)
The aim of the present exploratory study was to examine whether congruence exists between the organisational culture perceived to be evident at Compass, South Africa and the strategic objectives of the company. Information from the administration of the Harrison and Stokes (1992) instrument to measure existing and preferred organisational culture orientations was obtained from a sample of 86 employees representing two employee groupings at the company. The findings indicate that a difference in perception of the existing culture is evident between the CEO and the two employee groups and that there is a lack of alignment of the culture with the strategic objective of the company. The findings further suggest that there is consensus among the employee groups about the preferred culture that would appear to support the company strategy. Recommendations with regard to developing an organisational culture to support company strategic intent relate to the development of a learning organisation and the role of leadership in driving culture change.
Keywords: 650